Investigation of Changes in Color and Textural Quality Characteristics of Arugula (Eruca vesicaria) by Disinfectant Treatments - Janan Hossein Zadeh; Fikret Pazır (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to investigate the effects of the treatment of tap water (control), sodium hypochlorite (SH), electrolyzed oxidizing water (EOW), and hydrogen peroxide (HP) on the color, texture, and sensory properties of the Eruca vesicaria as a quality criterion. For this purpose, three different concentrations (25, 50, and 75 ppm) and three different times (1, 3, and 5 min) were applied in all three washing processes. There weren’t statistically significant differences in objective (color and texture) and subjective (sensory) results in all three washing processes in terms of both concentration and time. Thus, it was determined that these processes did not have a negative effect on the quality of green leafy vegetables.